The impact of unemployment on alcohol consumption: A panel data analysis - Nkomo, Nomusa Yolanda; Adanlawo, Eyitayo Francis (International Journal of Innovative Research and Scientific Studies, 2024)
Several books and articles published in the last few decades have looked at how alcohol use has affected the job market globally. This study attempted to determine how specific labour market shocks (such as losing a job) influence alcohol intake on an individual level to clarify the existing research. We went deeper into the subject of whether or not losing one's job increases the likelihood of alcohol abuse. We estimated models with fixed effects using panel data at the individual level from the National Income Dynamic Survey's Waves 1 and 5. (NIDS) to account for possible omitted variable bias. We calculated the gender-specific impacts of alterations in work status on the total intake of alcohol, occurrences of binge drinking and the diagnosis of alcohol addiction and dependency. The results consistently demonstrate a favorable and substantial impact of unemployment on drinking habits and these findings remain strong even when subjected to various robustness tests. The study concludes that being unemployed for more than a year causes people to consume less alcohol, perhaps as a result of financial stress. It is impossible to determine a precise cause-and-effect link but high unemployment rates may contribute to mental health problems including stress and depression which might be detrimental to public health. It is advisable to take into account the individual expenses and consequences related to alcohol consumption when making fiscal policy decisions aimed at boosting the economy particularly during economic recessions.